ОСОБЕННОСТИ ХИМИЧЕСКОГО СОСТАВА АМФИБОЛОВ ТАЛНАХСКОГО МЕДНО-НИКЕЛЕВОГО МЕСТОРОЖДЕНИЯ (СЕВЕРО-ЗАПАД СИБИРСКОЙ ПЛАТФОРМЫ) - Аплонов В.С.; Золотарев А.А. (My University, 2005)
Chemical composition of amphiboles was investigated in the well known Talnakh platinum-bearing cop-per-nickel ore field, for these minerals present as in rocks of ore-bearing intrusion, so in its metamorphic aureole. All studied amphiboles are calcium ones, among them were detected the following mineral species: tremolite-ac-tinolite, edenite, hastingsite, magnesiohastingsite, magnesian and ferrous hornblendes. Location of some mineral species correlates with particular geologic formations, and an attempt is made to coordinate features of chemical composition of those amphiboles with conditions of their formation.
Keywords: 549.643.02:553.481''43(-925.11/.16)